Vegetation and physicochemical analysis in sacred natural forests of Kumaun Himalaya - Sahani, Poonam; Kumar, Balwant; Bisht, Kapil; Tamta, Ritika (International Journal of Phytology Research, 2021)
The study of floristic diversity in any forest and its expansion are incomplete without taking consideration of plant-soil interactions. With this point, present study was undertaken in four temperate forests with three forest types i.e. banj- oak (Quercus leucotrichophora), rianj-oak (Q. lanuginosa) and mixed-oak (Quercus leucotrichophora, Q. floribunda & Q. lanuginosa) in Champawat, Kumaun Himalaya. The aim of the study was to assess the physical and chemical properties of soil in relation to the forest structure, composition and forest health. Chemical properties of the soil, i.e., total nitrogen (N), available phosphorus (P), available potassium (K), organic carbon (C), soil organic matter (SOM), pH and C:N ratios were analyzed for two different depths viz., (i) (0–15 cm), (ii) (15–30 cm) in all the selected forest types. Three plots each of 50 × 50 m were laid in each studied site at hill base, hill mid and hill top were laid. Phytosociological and diversity parameters viz. total basal cover (m2 ha-1), stem density (trees ha-1), tree species richness (SR), and Shannon–Wiener diversity index (H′) were also calculated for each forest type. The altitude doesn’t show any impact on the studied physicochemical properties of the soil whereas average organic matter shows a highly significant relationship with average carbon (r= 0.998; p<0.01). Potassium shows moderate significant relationship with average carbon and average organic matter (r= 0.610 and 0.622 respectively; p<0.05). Phosphorus shows slight significant relationship with Water Holding Capacity (WHC) of the soil (r= 0.588; p<0.05). No relationship between altitude and C was observed, which may be due to different composition of forest types along the altitudinal gradient and their differential decomposition rates. This study shows the stem density varied in between 606-1067 trees ha-1 and 45.20-71.78 m2 ha-1 total basal area was recorded from studied forest. The possible reason being luxuriant vegetation and undisturbed nature of these forest types due to their sacredness, which is evident from higher values of diversity and other phytosociological parameters.